Biological and molecular interactions between bell pepper endornavirus and two tobamoviruses - Escalante, Cesar; Khankhum, Surasak; Valverde, Rodrigo A. (Frontiers in Virology, 2023)
Peppers (Capsicum spp.) are native plants to the Americas. They are cultivated worldwide for direct human consumption and industrial purposes. Peppers can be infected by acute plant viruses, which cause a variety of diseases and crop losses. However, many Capsicum species can also be infected by persistent viruses. These are emerging viruses and they do not cause apparent disease and are transmitted only vertically. Using two near-isogenic lines of bell pepper cv. Marengo, biological and molecular interactions between the persistent virus bell pepper endornavirus (BPEV) and two acute viruses, pepper mild mottle virus (PMMoV) and tobacco mild green mosaic virus (TMGMV), were evaluated by symptom expression, enzyme-linked immunosorbent assay, and RT-qPCR. The relative titer of BPEV decreased at least two-fold at 14 days after infection when BPEV-infected plants were single infected with TMGMV or in mixed infection of PMMoV and TMGMV. The presence of BPEV was associated with symptom reduction in pepper plants infected with single and mixed infections of PMMoV and TMGMV. This suggests that the ubiquitous infection of BPEV may trigger the plant immune response, and therefore, BPEV is active when the plant is infected with PMMoV and/or TMGMV.